Análisis de la responsabilidad ulterior de los medios de comunicación como forma de limitar la libertad de prensa, opinión y pensamiento en los medios escritos de línea editorial en el Ecuador caso diario El Universo año 2011. Período septiembre a diciembre 2013. Lineamientos alternativos - Burbano de Lara Jijón, Bertha Karina (2014)
This research work : " ANALYSIS OF FURTHER RESPONSIBILITY OF THE MEDIA AS A WAY TO LIMIT THE PRESS FREEDOM VIEW AND THOUGHT IN BRIEFS MEDIA ONLINE PUBLISHING IN ECUADOR " EVENT DIARY THE UNIVERSE IN 2011 " . PERIOD SEPTEMBER TO DECEMBER 2013. ALTERNATIVE GUIDELINES", the same that was structured according to current regulation Graduation National University of Loja. Its overall objective: Conduct a critical character in the current situation being experienced investigative journalism , chiefly to the fact true, that the application of the " ultimate responsibility of the media " makes an "censorship prior " or" self-censorship " causing a kind of collective psychosis of fear, fear , retaliation, oppression and threats to citizens in general and , in particular towards those involved in the field of journalism , we exercise the noble work of spreading events , this feeling constrained and limited in the free exercise of investigative journalism way . Methods and techniques for data collection and data analysis were: the scientific method , the description , the Deductive and Statistical Model , techniques and instruments consist survey addressed reporters and views of people in general in order to : determine whether the application of the ( subsequent liability of the media ) leads to a " prior restraint " pose serious security irrigation investigative journalism and its sources and establish whether journalism as such or who exercise it , they look at the grueling task of " self-censorship " in order to avoid being punished and even intimidated, thereby restricting , the flow of information . With the implementation of the survey found that 60.50 % of the respondents state that the implementation of further liability to the media is a way to intimidate and stifle free speech and thought of the editors and media , 27.50 % do not consider the implementation of further liability to the media as a form of bullying and 12% partly considered plus 63% of respondents state that the fear of prosecution , may create self-censorship of the media and journalists , 26% do not think that the fear of prosecution believes self-censorship of the media and journalists , and 11% think that in part. Who we are immersed in the field of Social Communication, view with great concern the "ultimate responsibility of the media" the immediate effect of a coercive government profile. Who pretending " trasparentar information " has adopted a series of restrictive measures in all that is written or broadcast by the media, even to the point of criminalizing this noble activity , limiting and restricting thus everything relevant to freedom of the press review and thought, and in this specific case, for the purposes of this research, all that has to do with the press and the editorial line of Ecuador , taking as reference what happened in previous months with case " daily Universe " ( Emilio Palacios)